Improved Alveolar Dynamics and Structure After Alveolar Epithelial Type II Cell Transplantation in Bleomycin Induced Lung Fibrosis - Lopez-Rodriguez, Elena; Gay-Jordi, Gemma; Knudsen, Lars; Ochs, Matthias; Serrano-Mollar, Anna (Frontiers in Medicine, 2021)
Idiopathic pulmonary fibrosis (IPF) is a progressively and ultimately fatal lung disease. Previously it has been shown that intratracheal administration of alveolar epithelial type II cells (AE2C) in the animal model of bleomycin-induced pulmonary fibrosis is able to reverse fibrosis and restore surfactant protein levels. However, to date, it has not been evaluated whether these changes involve any improvement in alveolar dynamics. Consequently, the aim of the present work was to study lung physiology after AE2C transplantation at different time points during the development of injury and fibrosis. Lung fibrosis was induced by intratracheal instillation of bleomycin (4U/kg) in rat lungs. The animals were transplanted with AE2C (2.5x106 cells/animal) 3 or 7 days after bleomycin instillation. Assessments were done at day 7 and 14 after the induction of fibrosis to plot time dependent changes in lung physiology and mechanics. To assess the pressures and rates at which closed alveoli reopens invasive pulmonary tests using a small-animal mechanical ventilator (Flexivent®, Scireq, Canada) including de-recruitability tests and forced oscillation technique as well as quasi-static pressure volume loops were performed. Afterwards lungs were fixed by vascular perfusion and subjected to design-based stereological evaluation at light and electron microscopy level. AE2C delivered during the lung injury phase (3 days) of the disease are only able to slightly recover the volume of AE2C and volume fraction of LB in AE2C. However, it did not show either positive effects regarding ventilated alveolar surface nor any increase of lung compliance. On the other hand, when AE2C are delivered at the beginning of the fibrotic phase (7 days after bleomycin instillation), an increased ventilated alveolar surface to control levels and reduced septal wall thickness can be observed. Moreover, transplanted animals showed better lung performance, with increased inspiratory capacity and compliance. In addition, a detailed analysis of surfactant active forms (mainly tubular myelin, lamellar body (LB)-like structures and multilamellar vesicles (MLV)), showed an effective recovery during the pro-fibrotic phase due to the healthy AE2C transplantation. In conclusion, AE2C transplantation during fibrogenic phases of the disease improves lung performance, structure and surfactant ultrastructure in bleomycin-induced lung fibrosis